Emodin Protects SH-SY5Y Cells Against Zinc-Induced Synaptic Impairment and Oxidative Stress Through the ERK1/2 Pathway - Chen, Qian; Lai, Chencen; Chen, Fa; Ding, Yuanting; Zhou, Yiyuan; Su, Songbai; Ni, Ruiqing; Tang, Zhi (Frontiers in Pharmacology, 2022)
Zinc is an essential trace element important for the physiological function of the central nervous system. The abnormal accumulation of zinc inside neurons may induce mitochondrial dysfunction and oxidative stress, which contribute to many brain diseases. We hypothesized that natural anthraquinone derivative emodin can protect against neurotoxicity induced by pathological concentrations of zinc via the extracellular signal-regulated kinase 1/2 (ERK1/2) signaling pathway and alleviate oxidative stress and mitochondrial dysfunction. Human neuroblastoma (SH-SY5Y 26 cells) was treated with zinc sulfate and different concentrations of emodin, and changes in the levels of ETK1/2 expression, oxidative stress (DCFH-DA staining), mitochondrial function (JC-1 staining), lipid peroxidation (4-hydroxynonenal staining), and DNA oxidation (8-hydroxy-2-deoxyguanosine staining) were examined. Emodin ameliorated zinc-induced altered expression of levels of phosphorylated ERK1/2 (not total ETK1/2) and synaptic proteins (presynaptic SNAP 25, synaptophysin and postsynaptic PSD95) in SH-SY5Y cells. Moreover, emodin inhibited the generation of reactive oxygen substrates and oxidative stress and facilitated the collapse of mitochondrial membrane potential (ΔΨm) in SH-SY5Y cells. In conclusion, our results indicated that emodin exerts neuroprotective effects against zinc by normalizing synaptic impairment by decreasing the phosphorylation of ERK1/2, reducing reactive oxygen substrates and protecting mitochondrial function.